NOTCH Signaling Is Activated through Mechanical Strain in Human Bone Marrow-Derived Mesenchymal Stromal Cells - Fani Ziouti; Regina Ebert; Maximilian Rummler; Melanie Krug; Sigrid Müller-Deubert; Martin Lüdemann; Franz Jakob; Bettina M. Willie; Franziska Jundt (Hindawi Limited, 2019)
Skeletal development and remodeling of adult bone are critically controlled by activated NOTCH signaling in genetically modified mice. It is yet unclear whether NOTCH signaling is activated by mechanical strain sensed by bone cells. We found that expression of specific NOTCH target genes is induced after in vivo tibial mechanical loading in wild-type mice. We further applied mechanical strain through cyclic stretching in human bone marrow-derived mesenchymal stromal cells (BMSCs) in vitro by using a bioreactor system and detected upregulation of NOTCH target gene expression. Inhibition of the NOTCH pathway in primary BMSCs as well as telomerase-immortalized human BMSCs (hMSC-TERT) through the gamma-secretase inhibitor GSI XII blocked mechanotransduction and modulated actin cytoskeleton organization. Short-hairpin RNA gene silencing identified NOTCH2 as the key receptor mediating NOTCH effects on hMSC-TERT cells. Our data indicate a functional link between NOTCH activation and mechanotransduction in human BMSCs. We suggest that NOTCH signaling is an important contributor to molecular mechanisms that mediate the bone formation response to mechanical strain.